The Relationship Between Da'wah and Entrepreneurship: A Case Study on Inteam Group in Entertainment Industry in Malaysia - Nur Aimie Syarmimi J.; E. R., Fathiah , Z.; Masnih, M.; Khairunneezam, M. N.; Ambo Ahsan; Rafidah, M.N.; Affan Zahidi, A.A (GIAP Journals, 2024)
Purpose: Nasheed is an art and media of da’wah in Islam. In Malaysia, the songs of da’wah and divine is always welcome although various genres of new music are present. This study aims to examine the relationship between da’wah and entrepreneurship by one of the famous nasheed group in Malaysia which is Inteam.